Oral-health-related quality of life in adolescents: umbrella review - Ítalo Gustavo Martins Chimbinha; Brenda Nayara Carlos Ferreira; Giovana Pessoa Miranda; Renata Saraiva Guedes (BMC, 2023)
Abstract Background To evaluate oral conditions, demographic and socioeconomic characteristics of oral health-related quality of life (OHRQoL) in adolescents. Methods Umbrella review, conducted according to the Preferred Reporting Items for Systematic Reviews and Meta Analyzes (PRISMA) checklist. The search strategy used a combination of words, applied in the electronic databases PubMed, WebScience, Embase, Lilacs, Scopus and Cochrane. Included publications until January 2022, without restrictions. Data collection took place with systematized practices and the eligibility criteria were studies focusing on OHRQoL; teenagers; adolescentes; present the term "systematic review" and/or "meta-analysis" in the title or abstract. The quality assessment followed the Assessment of Multiple Systematic Reviews (AMSTAR 2) and the adherence of the article to the PRISMA was verified. Results Three hundred sixty-two articles were identified, and 22 were included, published between 2009 and 2022. 21 Systematic reviews focused on the English language. Most studies showed heterogeneity in the methodological structuring process: 10 articles were considered of low and 10 critically low quality. Clinical conditions associated with worsening in quality of life were dental caries, malocclusion, dental trauma, toothache, edentulism, need for orthodontic treatment, irregular brushing, and periodontal disease. Socioeconomic factors related to housing, parental education, access to health care, absence of siblings and nuclear family influence OHRQoL. Completion of orthodontic treatment, health promotion programs, dental care and safe housing all have a positive impact. Conclusion Worse oral health status, older age, female sex and worse socioeconomic status were significantly associated with worse OHRQoL. Trial registration PROSPERO CRD4202129352.